Industry and Intelligence Contemporary Art Since 1820 - Gillick, Liam 1964- (Columbia University Press, 2016)
The conceptual artist Liam Gillick writes a holistic genealogy of contemporary art, arguing that we need to appreciate its engagement with history, even when it seems apathetic or blind to current events. Rather than focus on dominant works or special cases, Gillick takes a broad view of artistic creation from 1820 to today, underscoring the industry and intelligence of artists as they have responded to incremental developments in science, politics, and technology